Vegelite: Carro-pop (plant based chicken popcorn) / Nurul Huda Othman ... [et al.] - Othman, Nurul Huda; Mad Rodi, Alia Shazwani; Awang, Aishah Maisyarah; Jaafar, Hani Fadeeha; Ghazali, Nur Adila Afifah; Zubir, Nur Fatihah (2023)
Carro-pop, a vegan popcorn that tastes like any other famous meat-based chicken popcorn due to the addition of Textured Vegetable Protein (TVP) that is made of soybean. This food product is made with the motivation of overcoming the problem of eating too much fat and sodium, as well as barely any nutrition snacks. Carro-pop, which can help fill an empty stomach, is especially vegan friendly because it is entirely made of carrot and free from any meat. It is also rich in essential nutrients such as protein and fibre and low in calories. Carro-Pop contains carrots, which are rich in beta-carotene, fibre, vitamin K1, potassium, and antioxidants. Our company, Vegelite, sells our product not only in shopping malls and retail stores but also virtually through shopping website of our own. Where consumers can easily order any quantity of their Carro-pop without having to worry about transportation fee and energy wasted. Our website is not only for ordering our Carro-Pop but it also allows anyone who has doubts about the credibility of this product to get knowledge of it. This is due to the website being well equipped with information, production, and history of the company as well as the research made along the way to achieve this product. Not to mention, we prove the most important aspect of making food production, which is that we have HACCP and GMP approval and also a MESTI certificate. Our company decides our products' overall acceptance and opinions through concept testing by conducting an online survey such as WhatsApp and Instagram. Thus, from this knowledge of public opinions, our packaging and price acceptance has been acknowledged. The company has been ongoing for 3 years and has managed to be not far behind other famous brands with the sales of RM 1,225,488 in the third year of our business. Needless to say, Vegelite is doing fine even though our company is still new.